2020
DOI: 10.1200/jco.19.02107
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Open-Label Study of Pembrolizumab in Treatment-Refractory, Microsatellite Instability–High/Mismatch Repair–Deficient Metastatic Colorectal Cancer: KEYNOTE-164

Abstract: PURPOSE KEYNOTE-164 (NCT02460198) evaluated the antitumor activity of pembrolizumab in previously treated, metastatic, microsatellite instability–high/mismatch repair–deficient (MSI-H/dMMR) colorectal cancer (CRC). METHODS This phase II open-label study involved 128 centers worldwide. Eligible patients were age ≥ 18 years and had metastatic MSI-H/dMMR CRC treated with ≥ 2 prior lines of standard therapy, including fluoropyrimidine, oxaliplatin, and irinotecan with or without anti–vascular endothelial growth fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
493
3
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 714 publications
(579 citation statements)
references
References 14 publications
17
493
3
6
Order By: Relevance
“…With the rising success rates of immunotherapy on cancers such as melanoma and non-small-cell lung carcinoma (NSCLC), clinical trials on other solid tumor such as CRC suggest a combination therapy approach to tackling tumors that have undergone immune evasion. Food and Drug Administration (FDA) approved CTLA4 inhibitors such as ipilimumab, PD1 inhibitor nivolumab and PD-L1 inhibitor pembrolizumab in high mismatch repair-deficient high metastatic CRC [12], along with newly emerging drugs in combination with or without radiotherapy are just some of the ongoing clinical trials on CRC patients. Single cell transcriptome analysis of tumor infiltrating T cells (TILs) gave rise to the identification of 20 different T cell subsets, each with distinct functions, associations and clonalities, highlighting the complex and dynamic relationship between T cell function and cancer [13].…”
Section: Introductionmentioning
confidence: 99%
“…With the rising success rates of immunotherapy on cancers such as melanoma and non-small-cell lung carcinoma (NSCLC), clinical trials on other solid tumor such as CRC suggest a combination therapy approach to tackling tumors that have undergone immune evasion. Food and Drug Administration (FDA) approved CTLA4 inhibitors such as ipilimumab, PD1 inhibitor nivolumab and PD-L1 inhibitor pembrolizumab in high mismatch repair-deficient high metastatic CRC [12], along with newly emerging drugs in combination with or without radiotherapy are just some of the ongoing clinical trials on CRC patients. Single cell transcriptome analysis of tumor infiltrating T cells (TILs) gave rise to the identification of 20 different T cell subsets, each with distinct functions, associations and clonalities, highlighting the complex and dynamic relationship between T cell function and cancer [13].…”
Section: Introductionmentioning
confidence: 99%
“…In colorectal cancer, checkpoint inhibitors such as pembrolizumab, nivolumab, and ipilimumab have been approved for MSI-H/dMMR metastatic colorectal cancer that has failed standard therapies (13)(14)(15)(16)(17). While studies on the benefits of palliative surgical interventions in the setting of malignant obstruction and fistula formation may have only suggested modest improvement in overall survival at best, these interventions were often followed by conventional chemotherapy or best supportive care in non-selected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Profound and durable responses with immunotherapy, however, has changed the expected OS of MSI-H CRC patients. Le et al demonstrated in a phase II study that MSI-H/dMMR mCRC patients who received pembrolizumab (anti-PD-1) achieved a 90% disease control rate, 78% immune-related progression-free survival (PFS) at 20 weeks, and an objective response rate of 30-40% (13). Nivolumab (anti-PD-1) has also shown clinical benefit [overall response rate (ORR), 31%; disease control rate, 69%; 12 month OS, 73%] in previously treated patients with MSI-H/dMMR mCRC (14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, Pembrolizumab, Nivolumab as well as the combination of Nivolumab and Ipilimumab have been approved by the Food and Drug Administration (FDA) for the treatment of MSI-H or dMMR metastatic CRC cases progressing after treatment with fluoropyrimidine, oxaliplatin, and irinotecan. An overview of selected clinical trials regarding these drugs can be found in Table 1 [16][17][18]. At the time of this writing, the European Medicine Agency (EMA) has not yet approved any of the aforementioned medicine for the treatment of MSI-H CRC.…”
Section: Approved Immune Checkpoint Inhibitors In Dmmr Mcrcmentioning
confidence: 99%